SEJARAH PEREKONOMIAN DAN SOSIAL BUDAYA INDONESIA (STUDI KASUS: PENAJAJAHAN JEPANG) - Mohammad Faeyza Azhari Dhoifullah (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2025)
The Dutch Colonial Policy continued to influence Indonesia's economy leading up to independence due to the Dutch economic focus on the development of plantation industries such as coffee, tobacco, rubber, palm oil, and sugar. During the Japanese occupation, the socio-economic conditions of Indonesian society underwent significant changes. The socio- economic life of Indonesia was greatly influenced by the Japanese occupation, which began in 1945. During the colonial period, the Japanese government implemented policies to maintain their dominance in Southeast Asia and to increase the production and utilization of Indonesia's natural resources.There are many different perspectives on the socio-economic conditions of Indonesian society during the Japanese occupation. First, the conflict between the ruling group and the non-ruling group causes the social structure of Indonesian society to change. When ordinary people struggle to meet their basic needs, members of the Indonesian elite, including businessmen and government officials, benefit from Japanese policies. Secondly, the Japanese government exploited Indonesian labor and took Indonesia's natural resources. Third, Indonesian culture and customs were destroyed and disrespected by the Japanese government.